Participation among youths and community development program in the Niger Delta Region of Nigeria - Chima, Nwaiwu James; Hamsan, Hanina Halimatusaadiah; Abu Samah, Asnarulkhadi (Center for Promoting Ideas, 2014)
The relationship of participation and the extent in which it can predict community development among youths is the major objective of this research. The study adopted a cross-sectional survey as its research design, using selfadministered questionnaire and simple random sampling as its sampling techniques. Sample size of 322 emerged from 2125 youths who benefited from Shell Petroleum Development Companies (SPDC’s) micro-credit loan designed for youths and business development based on the list of beneficiaries provided by the micro-credit scheme for agricultural development (MISCAD). Instrument of measurement for this study was derived from literatures in line with indicators of measuring each of the construct variables as the test and retest prove the instrument to be valid and reliable since the cronbach’s alpha of the constructs recording not less than 0.604. Findings from the outcome of the result show that there is strong relationship between participation and community development (CD) among youths with r = 0.238, p = 0.0002.Furthermore, participation was discovered as the major predictor of CD among youth. The study recommends that clear relationship between youth’s and supporting agencies should be increased and encouraged in CDY programs as further steps such as program design, proper information and orientation, integration and perceiving youths as resources and not problems will help in building this positive relationship.